2014
DOI: 10.1128/jcm.00696-14
|View full text |Cite
|
Sign up to set email alerts
|

New Clustered Regularly Interspaced Short Palindromic Repeat Locus Spacer Pair Typing Method Based on the Newly Incorporated Spacer for Salmonella enterica

Abstract: A clustered regularly interspaced short palindromic repeat (CRISPR) typing method has recently been developed and used for typing and subtyping of Salmonella spp., but it is complicated and labor intensive because it has to analyze all spacers in two CRISPR loci. Here, we developed a more convenient and efficient method, namely, CRISPR locus spacer pair typing (CLSPT), which only needs to analyze the two newly incorporated spacers adjoining the leader array in the two CRISPR loci. We analyzed a CRISPR array of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Studies have reported that trailer end spacers are generally conserved among different isolates and can be used to anchor clusters and detect common ancestors of the arrays and probably of the isolates themselves [ 9 ]. In contrast, the leader end spacers are usually polymorphic, reflecting the existence of distinctive phage/plasmid pools at a particular era in different geographic locations [ 8 ]. Ab-1 and Ab-107 were the first spacers acquired by the vast majority of our isolates ( S2 Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have reported that trailer end spacers are generally conserved among different isolates and can be used to anchor clusters and detect common ancestors of the arrays and probably of the isolates themselves [ 9 ]. In contrast, the leader end spacers are usually polymorphic, reflecting the existence of distinctive phage/plasmid pools at a particular era in different geographic locations [ 8 ]. Ab-1 and Ab-107 were the first spacers acquired by the vast majority of our isolates ( S2 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Due to their dynamic nature, comparative analysis of the arrays of spacers has successfully been used for subtyping isolates from several Gram-positive and-negative bacteria, including Mycobacterium tuberculosis , Yersinia pestis and the plant pathogen Erwinia amylovora (reviewed in [ 6 ]). Arrays of spacers were found to be highly polymorphic in Salmonella and a strong correlation was detected between polymorphisms in the arrays and the serotypes [ 7 , 8 ]. In fact, analyzing only newly incorporated spacers gave results that were highly consistent with traditional serotyping of Salmonella isolates [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two CRISPR regions 1 and 2 were amplified using specific primers. Several studies have reported the presence of two CRISPR loci in Salmonella (28). Within Salmonella, which contains the Type I-E CRISPR-Cas system (29), there are two CRISPR loci (CRISPR 1 and CRISPR 2) that differ in both the identity and number of spacers and repeats (30,31).…”
Section: F Analysis Of Spacer Regionsmentioning
confidence: 99%
“…8,9 Subtyping methods based on analyses of the spacers of the CRISPR loci have also been developed for Yersinia pestis and Salmonella. [10][11][12][13][14][15] Louwen and colleagues established that both spacer variation within the CRISPR array as well as single nucleotide polymorphisms in the cas genes were useful for typing Campylobacter jejuni. 16 There are also ongoing studies to apply the CRISPR-based typing system to other bacteria.…”
Section: Introductionmentioning
confidence: 99%